Evaluation of the mitigating effect of crack treatment on waterlogging stress in soybean - Yoshihiro Hirooka; Yasuhiro Izumi; Akihiro Sunami; Morio Iijima (Plant Production Science)
Waterlogging is a common environmental constraint that inhibits soybean growth and reduces its yield. The aim of the present study was to evaluate the alleviating effect of crack treatment during mid-term tillage on waterlogging stress in soybean using field and pot trials. In the field experiments, crack treatment significantly increased both biomass and seed production under a waterlogging condition by a short-term flood stress during the early growth stage. In the pot experiment, three factors, namely root cutting, nodule bacteria, and aeration, were separately evaluated using a double root chamber system. The results indicated that aeration significantly enhanced soybean yield in the waterlogged treatment. In addition, root cutting inhibited soybean growth, and nodule bacteria application had no significant effect. The findings suggest that the crack treatment mitigated waterlogging stress in field-grown soybeans, and that aeration is a key factor that mitigates waterlogging stress and influences soybean growth and yield.